Novel octa-graphene-like structures based on GaP and GaAs - Laranjeira, José A. S. [UNESP]; Martins, Nicolas F. [UNESP]; Azevedo, Sérgio A. [UNESP]; Fabris, Guilherme S. L.; Sambrano, Julio R. [UNESP] (Springer Nature, 2023)
Context: The discovery of graphene gave way to the search for new two-dimensional structures. In this regard, octa-graphene is a carbon allotrope consisting of 4- and 8-membered rings in a single planar sheet, drawing the research community’s attention to study their inorganic analogs. Considering the promising properties of octa-graphene-like structures and the role of GaAs and GaP in semiconductor physics, this study aims to propose, for the first time, two novel inorganics buckled nanosheets based on the octa-graphene structure, the octa-GaAs and octa-GaP. This work investigated the structural, electronic, and vibrational properties of these novel octa-graphene-based materials. The octa-GaP and octa-GaAs have an indirect band gap transition with a valence band maximum between M and Г points and a conduction band minimum at Г point with energy of 3.05 eV and 2.56 eV, respectively. The QTAIMC analysis indicates that both structures have incipient covalent in their bonds. The vibrational analysis demonstrates the occurrence of ΓRaman = 6Ag + 6Bg and ΓRaman = 12A′ + 12B″ for octa-GaP and octa-GaAs, respectively. The symmetry reduction of octa-GaAs leads to activating inactive modes observed in the octa-GaP structure. The frontier crystalline orbitals are composed by Ga(px) and P(py and pz) orbitals for octa-GaP and Ga(px and py) and As(s, py, and pz) for octa-GaAs in the valence bands while in the conduction bands by Ga(py, pz, and s) for both compounds and P(px and pz) and As(py). The phonon bands demonstrate the absence of the negative frequency modes and the structural stability of these new nanosheets. This report aims to reveal the fundamental properties of both newfound materials for stimulating experimental research groups in the search for synthesis routes to obtain this structure. Methods: This work used the DFT/B3LYP approach implemented in the CRYSTAL17 computational package. Ga, As, and P atomic centers were described by triple-zeta valence with polarization (TZVP) basis set. The vibrational analysis was carried out via coupled-perturbed Hartree–Fock/Kohn Sham (CPHF/KS) method, and the chemical bonds were evaluated via the quantum theory of atoms in molecules and crystals (QTAIMC).
Keywords: Buckling; GaAs; GaP; Octa-GaAs; Octa-GaP; Octa-graphene; T-graphene